PENINGKATAN KARAKTER RASA INGIN TAHU DAN HASIL BELAJAR MENGGUNAKAN MODEL PBL PADA MATERI KPK DAN FPB KELAS V SDN PLEBENGAN - Widyawati, Lydia; Puji Purnomo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of curiosity and learning outcomes of fifth-grade students at Plebengan Public Elementary School based on classroom observations and interviews with fifth-grade homeroom teachers. The data shows that the average curiosity of students is still in the low category, and learning outcomes in GCF and LCM material have not met the Learning Objective Achievement Criteria (KKTP) set by the school, which is 75.00. This study aims to increase the curiosity and learning outcomes of fifth-grade students at Plebengan State Elementary School through the application of the Problem-Based Learning (PBL) model in the material on KPK and FPB. This research is a Classroom Action Research (CAR). The research subjects are fifth-grade students at Plebengan State Elementary School in the 2025/2026 academic year. The data collection techniques used in this research are interviews, observations, questionnaires, and tests. The data analysis techniques used in this research are qualitative and quantitative data analysis. The results of the study indicate that the Problem-Based Learning (PBL) model can increase curiosity and learning outcomes through the following steps: 1) problem-oriented, 2) organizing students to learn, 3) investigating problems together in groups, 4) developing results and solving problems, 5) evaluating the problem-solving process. The average curiosity score of students increased from 53.47 (Low) at the beginning to 64.44 (Moderate) at the end of cycle I, and increased further to 85.35 (Very High) in cycle II. The average learning outcome score also increased from 59.82 at the beginning to 71.67 at the end of cycle I, and reached 82.22 at the end of cycle II. The application of the Problem-Based Learning (PBL) model proved to be effective, as seen from the N-gain score in the “High” category for curiosity with a result of 0.8527 or 85.27% in the “Effective” category. Then, the N-gain score for learning outcomes was in the “Moderate” category with a score of 0.5639 or 56.38% in the “Quite Effective” category.